Awareness, Facilitators, and Barriers to Policy Implementation Related to Obesity Prevention for Primary School Children in Malaysia - Chan, Camelina; Moy, Foong Ming; Lim, Jennifer N.W.; Dahlui, Maznah (SAGE Publications, 2018)
Purpose: To assess the awareness, facilitators, and barriers to policy implementation related to obesity prevention for primary school children. Design: A cross-sectional study administered using an online questionnaire. Setting: Conducted in 447 primary schools in a state in Malaysia. Participants: One school administrator from each school served as a participant. Measures: The questionnaires consisted of 32 items on awareness, policy implementation, and facilitators and barriers to policy implementation. Analysis: Descriptive analysis was used to describe the awareness, facilitators, and barriers of policies implementation. Association between schools’ characteristics and policy implementation was assessed using logistic regression. Results: The majority (90%) of school administrators were aware of the policies. However, only 50% to 70% of schools had implemented the policies fully. Reported barriers were lack of equipment, insufficient training, and limited time to complete implementation. Facilitators of policy implementation were commitment from the schools, staff members, students, and canteen operators. Policy implementation was comparable in all school types and locality; except the policy on “Food and Drinks sold at the school canteens” was implemented by more rural schools compared to urban schools (odds ratio: 1.74, 95% confidence interval: 1.13-2.69). Conclusion: Majority of the school administrators were aware of the existing policies; however, the implementation was only satisfactory. The identified barriers to policy implementation were modifiable and thus, the stakeholders should consider restrategizing plans in overcoming them.